Effect of different tetra pack juices on microhardness of direct tooth colored-restorative materials - Nazish Fatima; Syed Yawar Ali Abidi; Fazal-Ur-Rehaman Qazi; Shahbaz Ahmed Jat (Saudi Dental Journal)
Purpose: To examine the effect of apple and orange juices on the surface hardness of direct tooth-colored restorative materials. Materials and methods: The materials included resin-modified glass ionomer cement (Vitremer 3M™ ESPE™ Core buildup restorative) and composite resin (Filtek™ 3M™ ESPE™ Z350). A total of 45 disks of each restorative material were prepared. The disks were divided into groups of 15, which were immersed for 7 days in deionized water (G1/G4, control group), apple juice (G2/G5), or orange juice (G3/G6). The pH of the apple juice was approximately 4.8 and the pH of the orange juice was approximately 4.9. Surface hardness tests were performed before immersion and at various times following immersion. Statistical analysis included two-way ANOVA with repeated measurement and Tukey’s test. Results: Exposure to juices significantly reduced the hardness of both materials (p < 0.05), while deionized water did not affect the surface hardness of either material. The ionomer cement experienced a greater reduction than the composite resin (p = 0.000). There was no significant difference in the effect of apple and orange juices. Conclusion: Juice box-type fruit juices reduced the hardness of direct tooth-colored restorative materials. Material selection should be considered when planning restorations in patients who have experienced tooth surface loss. In terms of the materials evaluated in this study, the composite material provides greater durability under acidic conditions. Keywords: Esthetic restorative material, Erosion, Resin modified glass ionomer, Resin composite, Surface microhardness, Fruit juices